Azole non-susceptible C. tropicalis and polyclonal spread of C. albicans in Central Vietnam hospitals - Ngo, Thi Minh Chau; Santona, Antonella; Fiamma, Maura; Ton Nu, Phuong Anh; Do, Thi Bich Thao; Cappuccinelli, Piero; Paglietti, Bianca (The Journal of Infection in Developing Countries, 2023)
Introduction: Candida spp. are responsible for infections ranging from local to systemic, and resistance to antifungal first-line therapy is increasing in non-albicans Candida species. We aimed to determine the etiology of candidiasis and the antifungal resistance of Candida spp. isolated in Hue hospitals, Central-Vietnam. Methods: Species identification was performed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry supported by fungal internal-transcribed-spacer amplification and sequencing. Antifungal susceptibility testing was performed by disk diffusion method and minimum inhibitory concentrations of azoles, caspofungin, and amphotericin B against C. tropicalis were determined by broth microdilution. Polymorphism of erg11 gene associated with fluconazole resistance was carried out by polymerase chain reaction and sequencing. Multilocus sequence typing (MLST) was used for typing selected C. albicans isolates. Results: Overall, 196 Candida isolates were detected, mostly C. albicans (48%), followed by C. tropicalis (16%), C. parapsilosis (11%), C. glabrata (9%), C. orthopsilosis (6%) and to a lesser extent another eight species. High rates of resistance to fluconazole and voriconazole (18.8%) were observed in C. tropicalis with five isolates co-resistant to both agents. Y132F and S154F missense mutations in the ERG11 protein were associated with fluconazole-resistance in C. tropicalis (67.7%). Resistance to caspofungin was found in one isolate of C. albicans. MLST identified a polyclonal population of C. albicans with multiple diploid sequence types, and with few lineages showing potential nosocomial spread. Conclusions: Resistance to triazole agents should be considered in C. tropicalis infections in the studied hospitals, and surveillance measures taken to avoid Candida diffusion.